South Africa in records from colonial missionaries, 1819-1900. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2013)
In South Africa, the United Society for the Propagation of the Gospel began its labours at the Cape in 1821, the western division being occupied in that year and the eastern division in 1830. The society's work made a limited impact until the arrival of Robert Gray (consecrated Bishop of Capetown in 1847), under whom, from 1847 to 1872, and subsequently, the work spread at an unprecedented rate. Natal was occupied in 1849, Kaffraria in 1855, and Zululand in 1859. During the period 1752-1906 the Society expended £1,092,009 and employed 668 ordained missionaries in Africa. This collection from the Archives of the United Society for the Propagation of the Gospel, dates from their earliest connection with South Africa. Since January 1965 the USPG continues the work previously done by the SPG (incorporated 1701) and UMCA, the Universities' Mission to Central Africa, founded in 1857 in response to Livingstone's challenge at Cambridge. Both are Anglican societies. As the USPG is a church society, their records are arranged by dioceses, as this is the administrative and geographical unit with which they dealt. The original MSS are mainly in bound volumes and these fall into two series. Series D contains all of the letters written to the SPG, mainly by the bishop and some missionaries, but also by other persons such as administrators. Series E contains the Annual Reports, which each missionary was expected to send home about the area and his work there. After the earliest years one, or sometimes two, annual volumes are required to contain African records in each series. Series D begins in 1850, Series E in 1856, but earlier papers have been filmed, either from series E/Pre/J or from the various boxes of unbound letters that comprise C/AFS. The letter C distinguishes all unbound papers, and AFS denotes 'Africa South'. The numbering of the volumes was abandoned after vol. 95 of 1895 in D, and vol. 45 of 1890 in E. Thereafter reference is by year, e.g. D. 1896. Description derived from an Introduction by Isobel Pridmore of the USPG and 'The Churchman's Missionary Atlas' p.32;" see catalogue listing to view these items.
Date range: 1819-1900.
Keywords: Missions -- South Africa -- History -- 18th century; Missions -- South Africa -- History -- 19th century; United Society for the Propagation of the Gospel